2006
DOI: 10.1002/ejoc.200600063
|View full text |Cite
|
Sign up to set email alerts
|

N′‐(3‐Amino‐1H‐isoindol‐1‐ylidene)‐R‐carbohydrazides and Their Amide‐Type Isomerism

Abstract: A series of NЈ- (3-amino-1H-isoindol-1-ylidene)alkyl (aryl,heteroaryl)carbohydrazides have been synthesized in good yields and their structure and conformational behavior in the solid state and in solution have been studied by X-ray crystallography, NMR spectroscopy, and quantum calculations. (E)/(Z) amide-type isomerism and the dependence of the iso-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Recently, the crystal structures and biological properties of a large number of hydrazone derivatives and their metal complexes have been reported [1][2][3][4][5]. As part of the ongoing investigation of this class of compounds, the crystal structure of anew hydrazone derivative is reported in this paper.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, the crystal structures and biological properties of a large number of hydrazone derivatives and their metal complexes have been reported [1][2][3][4][5]. As part of the ongoing investigation of this class of compounds, the crystal structure of anew hydrazone derivative is reported in this paper.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular structure of the title compound consists of a [3,4]dioxolebenzohydrazide and a2 -chloro-5-nitrobenzylidene groups that are located on opposite sides of the C=N bond showing an E configuration. The dihedral angle between the two substituted benzene rings C1-C6 and C9-C14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may assume that these compounds are similar in structure to previously studied N',N"-1H-isoindole-1,3-diylidenedicarbohydrazides and exist in a symmetrical tautomeric form. We should note that the disubstitution products also could not be obtained in a similar reaction from phthalodinitrile [8]. However, they can be synthesized either from 1,3-substituted 1H-isoindoles -from highly reactive 1,1,3-trichloro-1H-isoindole [24] or from 1-imino-1H-isoindole-3-amine [25].…”
mentioning
confidence: 99%
“…The reaction of dinitrile 5 with an equivalent amount of hydrazides was carried out by the method described by Hordiyenko et al [8]. Analysis of the mixture of crude products by LC/MS showed that all the hydrazides taken, except cyclopropanecarboxylic acid hydrazide, react with dinitrile 5 to give a mixture of structural isomers, N'- (7-amino-2,4-dimethyl-5H-pyrrolo[3,4-b]pyridin-5-ylidene)carbohydrazides 6b-d and N'- (5-amino-2,4-dimethyl-7H-pyrrolo[3,4-b]pyridin-7-ylidene)carbohydrazides 7b-d.…”
mentioning
confidence: 99%